Measuring Hotel Channel Mix: A DEA-BSC Model. (February 2019) - Dolasinski, Mary Jo; Roberts, Chris; Zheng, Tianshu
The hotel industry has experienced changes brought on by growth, customer expectations, and the proliferation in the use of e-commerce and online distribution channels. Future hotel success depends on how effectively hotel revenue managers are able to manage different booking channels to maximize hotel revenue. A Data Envelopment Analysis–Balanced Scorecard (DEA-BSC) model to measure efficiency of distribution channel mix using BSC results is presented. DEA-BSC was used because DEA-BSC incorporates multiple metrics simultaneously while traditional business models typically focus on one performance measure such as profit. Inputs for the model include the five distribution channels of C-Res/Voice, GDS, Brand.com, OTAs, and property/relationship sales. Output is the consolidated BSC average. The model was tested and results presented, demonstrating support for the usefulness of the model.